2016
DOI: 10.5851/kosfa.2016.36.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Pork Quality Traits According to Postmortem pH and Temperature in Berkshire

Abstract: This study was performed to investigate the role of pH and temperature postmortem, and to demonstrate the importance of these factors in determining meat quality. Postmortem pH45min (pH at 45 min postmortem or initial pH) via analysis of Pearson’s correlation showed high positive correlation with pH change pHc24 (pH change from pH45min to pH24h postmortem). However, postmortem pH after 24 h (pH24h or ultimate pH) had a high negative correlation with pH change, pHc24, CIE L*, and protein content. Initial temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
3
25
0
2
Order By: Relevance
“…Kim et al. () showed that WHC is directly associated with muscle pH, whereas Tang, Yu, Zhang, and Bao () found negative correlation between WBS and pH. Protein, IMF and ash contents were not influenced by high pre‐slaughter environmental temperature ( p > .05; Table ) and their average contents (20.95, 6.65, and 1.14/100 g meat, respectively) were similar to those found in our previous study (Perna et al., ).…”
Section: Resultssupporting
confidence: 84%
“…Kim et al. () showed that WHC is directly associated with muscle pH, whereas Tang, Yu, Zhang, and Bao () found negative correlation between WBS and pH. Protein, IMF and ash contents were not influenced by high pre‐slaughter environmental temperature ( p > .05; Table ) and their average contents (20.95, 6.65, and 1.14/100 g meat, respectively) were similar to those found in our previous study (Perna et al., ).…”
Section: Resultssupporting
confidence: 84%
“…The consumer demands for high quality meat is increasing in most countries, so high-quality meat production is important to satisfy the buying public and to render the pork industry competitive. To produce high-quality meat, it is necessary to understand the meat quality characteristics and the factors to control them (Kim et al 2016). These include pH, color, tenderness, waterholding capacity (WHC), and chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that drip loss was a negatively correlated to pH 24 h post‐mortem ( r = −0.40) (Kim et al . ). The faster pH decline causes denaturation of sarcoplasmic and myofibrillar proteins, resulting in reduced water‐holding capacity (Scheffler & Gerrard ).…”
Section: Discussionmentioning
confidence: 97%